Vanessa Bell’s Attic studio at Charleston: Its History, Impact and Future - Diana Wilkins (Janeway JS, 2019)
The artist, Vanessa Bell (1879-1961), used the attic studio at Charleston Farmhouse in Sussex for the last twenty years of her career. Her son felt that Bell’s move to a studio at the top of the house was linked to her reclusive nature, but the original plans for the studio indicate more complex reasons. The most important factors may have been the need to provide extra working space and to accommodate Bell’s family who sought refuge at Charleston ahead of the Second World War. Initially, Bell had planned a large new studio on the ground floor, but she economised by creating three smaller studios, including one in the attic, away from visitors and domestic demands. Working in the attic studio, Bell created subtle compositions and searching self-portraits that often incorporate the room’s physical characteristics. Reappraising Bell’s achievements during these years provides a more balanced picture of her late style, which has sometimes been clouded by a narrative of withdrawal and inferred decline. Returning the studio to a museum space open to the public would help preserve Bell’s legacy by allowing visitors to immerse themselves in her final working environment.